Classification of decomposable Manin triples and solutions of the classical Yang-Baxter equation - Pantev, Tony; Tsanov, Vasil (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1995)
We classify decomposable triple Manin over an arbitrary smooth algebraic curve and describe the corresponding solutions of the classical Yang-Baxter equation. We also give some examples and countar-examples clarifying the nature of the correspondence between general triple Manin systems and solutions of the classical yang-Baxter equation.